2001
DOI: 10.1080/00480169.2001.36214
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of calcium absorption and reduction in susceptibility to fasting-induced hypocalcaemia in pregnant ewes fed vegetable oil

Abstract: Susceptibility of late-pregnant ewes to fasting-induced hypocalcaemia was reduced using a soya bean oil supplement. The inclusion of one or more dietary ingredients capable of binding or forming complexes specifically with Ca in the diet of late pregnant ruminants may provide a novel, practical method of reducing periparturient hypocalcaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
1
1
Order By: Relevance
“…This increase might be due to increase in phospholipid contents in CSFA. The results disagree with that of Wilson [35] and Ghattas and Nasra [10], and these differences might be due to dose difference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This increase might be due to increase in phospholipid contents in CSFA. The results disagree with that of Wilson [35] and Ghattas and Nasra [10], and these differences might be due to dose difference.…”
Section: Discussioncontrasting
confidence: 99%
“…These results agree with that obtained by Wilson [35], Abo-Donia et al [36], and Ghattas and Nasra [10]. Moreover, the results of the present study revealed significant increase in serum phosphorous levels and significant decrease in the Ca/P ratio after four weeks of treatment compared with control.…”
Section: Discussionsupporting
confidence: 93%
“…(2002b, 2003) described positive results in feeding zeolites. Wilson (2001a,b) also reports preventive effects in ewes that were fed soy oil. Also, Katsoulos et al.…”
Section: Introductionmentioning
confidence: 99%